Effect of Inter and Intra-Row Spacings on Grain Yield of Rainfed Cluster Bean - Kacker, N L; Daulay, H S; Singh, R P (Annals of Arid Zone, 2016)
A field experiment on the effect of inter and intra-row spacings on branched and single stemmed clusterbean varieties was carried out on light texture loamy sand soils of CAZRI, Regional Research Station, Bikaner Farm during monsoon seasons of 1977,1978 and 1980. During 1978 and 1980 seasons, branched variety Durgajay gave significantly higher yield than single stemmed FS.277. There were no significant differences in grain yield due to intra-row spacings during 1977 and 1978 seasons. However in 1980, an acute drought year, narrow row spacing (30 cm) gave significantiy higher yield than the 45 and 60 cm row spacings. In 1978 and 1980 seasons intra-row spacing of 15 cm resulted in significantly increased yield over 22.5 cm spacing. Interaction effects of varieties x inter and intra-row spacings did not influence the grain yield of clusterbean significantly.